تحديد البارامترات التصميمية لاستقرار المنصات البحرية الثابتة (Jacket) في الساحل السوري باستخدام النمذجة الحاسوبية - إبراهيم عدنان; الحسن محار (Latakia University Journal -Engineering Sciences Series, 2018)
The efficiency of offshore platforms and their safe design depend on a complex structure of mutual influence between these installations on the one hand and the surrounding environment and on the degree of resistance to different loading patterns during the entire investment period. The fixed platform of the Jacket is a large metal frame facility used to explore and extract oil and gas. The main function of the marine platform is to ensure the stability of the upper section above it, with all the facilities included in operating conditions, normal and unusual (weather conditions). In addition, the platform must be designed to be fully capable of resisting various environmental loads. Many studies have shown that the rise of sea wind waves plays a major role in the design of marine platforms compared to other environmental factors. The statistical analysis of the Jacket marine platform was carried out using the SACS program after building the model and applying the environmental loads according to three loading cases (45,90,135) according to the trends of the wind waves on the Syrian coast (southwest, west, north west). After comparing the values ​​of the base shear and overturning moments according to three loading cases, the maximum value of each of them occurs in the direction of the south-west loading. The stress ratio applied to all elements compared with the stress allowed under storm conditions (Unity Check) (UC <1) is verified according to the design code (API) and thus It is in normal operating conditions, and even in the marine platform storm conditions will be able to withstand and Achieving safety . تعتمد كفاءة المنصات البحرية وتصميمها الآمن على تركيب معقد من التأثير المتبادل بين هذه المنشآت من جهة، والبيئة المحيطة بها، وعلى درجة مقاومتها لأنماط التحميل المختلفة خلال كامل فترة استثمارها. المنصة الثابتة من نوع (Jacket) هي منشأة إطارية معدنية ضخمة تستخدم لاستكشاف واستخراج النفط والغاز. تتمثل المهمة الرئيسية للمنصة البحرية في تأمين استقرار القسم العلوي المحمول فوقها، بكل ما يتضمنه من منشآت في ظروف التشغيل، العادية وغير العادية (ظروف الطقس العاصف). بالإضافة إلى ذلك يجب أن تصمم المنصة بحيث تكون قادرة تماماً على مقاومة مختلف الحمولات البيئية. وقد أثبتت العديد من الدراسات أن لارتفاع أمواج الرياح البحرية الدور الأساسي والمسيطر في تصميم المنصات البحرية مقارنة مع باقي العوامل البيئية الأخرى. تم إجراء التحليل الستاتيكي للمنصة البحرية من نوع (jacket) بأربع قوائم على عمق (79.5m) باستخدام برنامج (SACS) وذلك بعد بناء النموذج وتطبيق الحمولات البيئية (الأمواج, الرياح) وفقاً لثلاث حالات تحميل وفق الزوايا ((450,900,1350 مع خط الاتجاه (جنوب – شمال)، تبعاً للاتجاهات المسيطرة لأمواج الرياح المؤثرة على الساحل السوري (الجنوب الغربي, الغرب, الشمال الغربي). بالمقارنة بين قيم قوى القص وعزوم الانعطاف الناتجة عن حالات التحميل الثلاث يتبين أن القيمة العظمى لكل منهما تحدث وفق الاتجاه الجنوبي الغربي. وأن) Unity Check نسبة الإجهاد المطبق على العنصر مقارنة مع الإجهاد المسموح والمعروف اختصاراً بالرمز UC) لجميع العناصر في ظروف العاصفة (UC<1) وهي قيم محققة وفقاً لكود التصميم (API). وبالتالي فإنه في ظروف التشغيل العادية وحتى في ظروف العاصفة فإن المنصة البحرية المفترضة ستكون قادرة على الصمود وتحقيق الأمان المطلوب.